Transient multipath analysis of circular cylinders above sinusoidal surfaces using a ray tracing method - Kizilay, A; Rothwell, EJ (VSP BV, 2004)
The deterministic problem of transient, short-pulse scattering from a perfect electric conductor cylinder above flat and sinusoidal surfaces is undertaken. Previous work for the ultra-wide band analysis of both TE (vertical) and TM (horizontal) polarizations are utilized to solve this scattering problem. The possible paths traveled by the reflected waves are calculated and the multiple reflections are identified by using timing analysis. Transient multipath effects for a cylinder above a sinusoidal surface are contrasted with those for a cylinder above a flat surface.
Keywords: INFINITE PERIODIC SURFACE; SCATTERING; Engineering; Physics